Method for growing hydroxyapatite on titanium rod based on hydrothermal method

By growing a hydroxyapatite coating on a titanium rod using a hydrothermal method, the problems of high energy consumption, complex process, and poor coating uniformity in titanium-based implant surface modification methods are solved, low-temperature, efficient coating preparation is achieved, and the bone integration performance and implant stability are improved.

CN120617625APending Publication Date: 2025-09-12BAOJI JIAQI METAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510756251.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-08
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

In the existing technology, titanium-based implant surface modification methods have problems such as high energy consumption, complex processes, poor coating uniformity and weak bonding force, which affect the bone integration performance and long-term stability of the implant.

Method used

A hydrothermal method is used to grow a hydroxyapatite coating on a titanium rod. By controlling the appropriate reaction temperature, time and pH value in a closed reactor, a high-pressure environment is used to achieve directional and uniform growth of HA crystals, forming a dense, highly crystalline coating.

Benefits of technology

It reduces the reaction temperature and energy consumption, improves the uniformity and bonding strength of the coating, enhances the bonding ability between the titanium rod and bone tissue, adapts to the coating of complex shapes, and does not require high-temperature annealing treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120617625A_ABST
    Figure CN120617625A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for in-situ growth of a hydroxyapatite coating on the surface of a titanium rod based on a hydrothermal method, and belongs to the technical field of biomedical materials. According to the method, by optimizing a hydrothermal reaction process, a hydroxyapatite coating with high bonding strength and excellent biological activity is formed on the surface of a titanium substrate, and the osseointegration performance of the titanium implant is remarkably improved. The process is simple and environment-friendly, and the obtained HA coating is firmly combined with the titanium substrate, has good biological activity and mechanical stability, can promote adhesion and growth of bone cells, and is suitable for long-term implantation instruments such as artificial joints and tooth root implants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials. Specifically, it relates to a method for in-situ growing a hydroxyapatite (HA) coating on the surface of a titanium or titanium alloy rod through a hydrothermal reaction. The coating can significantly improve the bone integration performance of titanium-based implants and is suitable for orthopedic and dental implants. Background Art

[0002] Titanium and its alloys have excellent biocompatibility, high specific strength, corrosion resistance and good mechanical properties, and are therefore widely used in orthopedic and dental implant materials (such as artificial joints, dental implants and bone screws, etc.). However, titanium itself is a bioinert material with limited direct bonding ability between its surface and bone tissue, which may lead to insufficient bone integration and thus prolong the bone integration period, affecting the long-term stability of the implant. In addition, the elastic modulus of titanium is much higher than that of cortical bone, which easily induces a stress shielding effect, which is likely to cause absorption and loosening of the implanted bone. Hydroxyapatite (Ca 10 (PO4)6(OH)2, HA) is the main inorganic component of human bones and teeth. It has excellent bioactivity, osteoconductivity and chemical stability. Constructing an HA coating on the surface of titanium implants can significantly improve the bone integration ability of the implants.

[0003] Traditional methods for modifying titanium surfaces include plasma spraying, electrochemical deposition, and sol-gel methods. Among them, plasma spraying is to melt HA powder at high temperature (>10000 ℃) and then spray it, but there are problems such as high temperature phase change and weak bonding strength. Electrochemical deposition is to melt HA powder containing Ca 2+ and PO4 3- The electrolyte is electroplated for deposition, but hydrogen bubbles are easily mixed in the electrolyte to form holes on the coating surface, resulting in reduced purity of the coating surface and poor crystallinity. The sol-gel method requires multiple coatings and high-temperature sintering during the preparation process. The presence of shrinkage stress during drying can easily lead to the formation of a crack network, and the subsequent sintering process can easily cause the Ca / P ratio to deviate. The hydrothermal method is a low-temperature wet chemical synthesis technology with a relatively low reaction temperature, generally between 120-200 °C. Low temperature can avoid phase change of the titanium matrix and thermal decomposition of HA, but the existing hydrothermal process has the problems of complex process and poor uniformity and weak bonding of the prepared coating. Summary of the Invention

[0004] Given that traditional methods have high energy consumption, harsh reaction conditions, high costs, and difficulty in regulating the morphology of HA, the purpose of the present invention is to provide a low-temperature, high-efficiency, high-bonding-strength HA coating preparation method to reduce costs while solving the problems of poor coating uniformity and complex processes in the prior art.

[0005] In order to achieve the above-mentioned technical purpose of the present invention, the inventors conducted a large number of experimental studies and unremitting explorations, and finally adopted a hydrothermal method in a closed reactor and screened suitable reaction parameters such as temperature and time, while using a high-pressure environment to achieve directional and uniform growth of HA crystals on the titanium surface, thereby growing a dense, highly crystalline, morphologically controllable, and strongly binding hydroxyapatite coating on the titanium rod.

[0006] Specifically, the technical solution of the present invention includes the following: a method for growing hydroxyapatite on a titanium rod based on a hydrothermal method, the method comprising the following steps:

[0007] (1) Take a titanium rod, polish it until the surface is smooth to remove the surface oxide layer, and then clean the titanium rod;

[0008] (2) Immerse the cleaned titanium rod in a 4-6 mol / L NaOH solution and react at 50-70 °C for 5-7 h to obtain a titanium rod with a porous surface, which facilitates the subsequent nucleation and adhesion of hydroxyapatite;

[0009] (3) Prepare a 0.5-0.9 mol / L hydroxyapatite precursor solution, adjust the pH to 10 with ammonia water, and continue stirring for 20-40 min;

[0010] (4) After stirring, the hydroxyapatite precursor solution is transferred to a hydrothermal reactor, and the porous titanium rod obtained in step (2) is immersed therein. The reactor is then placed in a homogeneous reactor, and the temperature is raised to 170-200 °C at a rate of 4-6 °C / min and kept at this temperature for 18-30 h;

[0011] (5) After the reaction is completed, the titanium rod is cleaned with anhydrous ethanol and deionized water and then dried.

[0012] It should be noted that the method for preparing the hydroxyapatite precursor solution in step 3 is as follows: taking the Ca / P atomic ratio of 1.67 and the concentration of hydroxyapatite of 0.5 mol / L as an example, it is calculated that 1.5 g Ca(NO3)2·4H2O, 0.5 g (NH4)2HPO4 and 20.26 mL deionized water are required. The deionized water is divided into two equal parts, and Ca(NO3)2·4H2O and (NH4)2HPO4 are added to the deionized water respectively to prepare solution A (containing Ca 2+ ) and liquid B (containing NH4 + ), slowly add liquid B to liquid A, adjust the pH to 10 with ammonia, and continue stirring for about 30 minutes. After the hydrothermal reaction in step (4) is completed, wait until it cools to room temperature before opening it to avoid excessive pressure inside the reactor, which may cause the solution to splash and injure people when opening the reactor.

[0013] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, in step (1), the titanium rod is polished using 600# and 2000# sandpapers in sequence until the surface is smooth.

[0014] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, the method for cleaning the titanium rod in step (1) is to use acetone, ethanol, and deionized water for ultrasonic cleaning in sequence for 10-20 minutes.

[0015] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, the Ca / P atomic ratio of the hydroxyapatite precursor solution prepared in step (3) is 1.67.

[0016] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, the concentration of the hydroxyapatite precursor solution prepared in step (3) is 0.5-0.6 mol / L.

[0017] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, the reaction heating rate in step (4) is controlled at 5°C / min, and the holding time is controlled at 22-24h.

[0018] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, the drying temperature in step (6) is 55-65°C and the drying time is 8-15 h.

[0019] Further preferably, in the method for growing hydroxyapatite on a titanium rod based on a hydrothermal method as described above, the titanium rod is made of pure titanium or a titanium alloy.

[0020] Compared with the prior art, the present invention provides a method for growing hydroxyapatite on a titanium rod based on a hydrothermal method, which uses a homogeneous reactor to conduct hydrothermal reaction experiments and has the following advantages and significant progress:

[0021] (1) The reaction temperature in the present invention is low. Compared with existing methods for preparing hydroxyapatite coatings, such as plasma spraying, which requires extremely high temperatures (>10,000 °C) at which HA easily undergoes phase change, the temperature used in the present invention is 200 °C, which greatly reduces the reaction temperature. Not only does it prevent HA from undergoing phase change, but it also reduces the reaction energy consumption.

[0022] (2) Compared with the electrochemical deposition method, the hydrothermal method used in the present invention has the characteristics of high crystallinity, uniform surface coating, and controllable composition. The electrochemical deposition method is carried out at room temperature, which results in low HA crystallinity and is prone to hydrogen evolution at the cathode, forming uneven holes and pores on the surface of the titanium rod. In addition, a subsequent heat treatment step is required after electrochemical deposition, annealing at 600°C. Heat treatment can easily lead to oxidation of the titanium surface and reduce interfacial bonding strength. The hydrothermal method of the present invention is relatively simple and does not require annealing.

[0023] (3) The HA coating obtained by the present invention has a strong bonding ability with the titanium rod substrate. It directly forms chemical bonds by nucleation on the titanium surface through in situ growth. The bonding strength is significantly higher than that of physical coating methods. It can be applied to titanium rods with complex shapes. The coating is uniform and does not easily fall off. In addition, the hydrothermal reaction of the present invention does not require an organic solvent, the residue after the reaction is easy to clean, and it has excellent biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD pattern of the titanium rod without HA coating.

[0025] Figure 2 is a surface SEM image of a titanium rod not coated with HA.

[0026] Figure 3 It is the EDS spectrum and mapping diagram of the titanium rod without HA coating.

[0027] Figure 4 This is the XRD pattern of the titanium rod coated with HA in Example 1.

[0028] Figure 5 This is the Raman spectrum of the titanium rod coated with HA in Example 1.

[0029] Figure 6 1 is a surface SEM image of the titanium rod coated with HA in Example 1.

[0030] Figure 7 This is the EDS spectrum and mapping diagram of the titanium rod after being coated with HA in Example 1.

[0031] Figure 8 1 is the XRD pattern of the titanium rod coated with HA at 150°C and 180°C in Example 3.

[0032] Figure 9 1 is the XRD pattern of the titanium rod after coating with HA in Example 4 at 12 h and 24 h.

[0033] Figure 10 1 is the XRD pattern of the titanium rod after coating with HA at pH 7 and 10 in Example 5. DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention are further described below. In order to make the objects, solutions and advantages of the present invention clearer, the technical solutions and technical effects of the present invention will be clearly and completely described below in conjunction with specific embodiments and accompanying drawings. Unless otherwise indicated, the terms used herein have the usual meanings in the art. However, it should be understood that the embodiments are merely exemplary and do not constitute any limitation to the scope of protection of the present invention. It should also be understood by those skilled in the art that the details and forms of the technical solutions can be modified or replaced without departing from the spirit of the present invention, but these modifications or replacements all fall within the scope of protection of the present invention.

[0035] Example 1: Hydrothermal growth of hydroxyapatite on titanium rods

[0036] (1) Use 600# and 2000# sandpaper to polish the titanium rod until the surface is smooth, and then use acetone, anhydrous ethanol and deionized water to ultrasonically clean the titanium rod for 15 min respectively.

[0037] (2) Alkali heat treatment: prepare a 5 mol / L NaOH solution and place the polished and cleaned titanium rod in it for reaction at 60 °C for 6 h to obtain a titanium rod with a porous surface, which is convenient for the subsequent nucleation and adhesion of hydroxyapatite.

[0038] (3) Prepare the hydroxyapatite precursor solution with a Ca / P atomic ratio of 1.67 and a mixed solution concentration of 0.5 mol / L. Calculate that 1.5 g Ca(NO3)2·4H2O, 0.5 g (NH4)2HPO4, and 20.26 mL deionized water are required. Divide the deionized water into two equal parts, and add the weighed Ca(NO3)2·4H2O and (NH4)2HPO4 into the deionized water to prepare solution A (containing Ca 2+ ) and liquid B (containing NH4 + ), slowly add solution B into solution A, adjust the pH value to 10 with ammonia water, and continue stirring for 30 min.

[0039] (4) After stirring, the hydroxyapatite precursor solution was transferred to a hydrothermal reactor, and a porous titanium rod was immersed in the reactor. The reactor was then placed in a homogeneous reactor, and the temperature was raised to 180 °C at a rate of 5 °C / min and kept at this temperature for 24 h.

[0040] (5) After the reaction, the titanium rod was washed with anhydrous ethanol and deionized water several times and then dried at 60 °C for 12 h.

[0041] Example 2: Effect of different Ca / P atomic ratios on hydroxyapatite growth

[0042] X-ray diffraction (XRD) tests were performed on the hydroxyapatite produced by varying the Ca / P atomic ratio. The results showed that when the Ca / P atomic ratio was 1.67, pure hydroxyapatite with good crystallinity could be produced.

[0043] Example 3: Effect of different hydrothermal reaction temperatures on hydroxyapatite growth

[0044] The effects of different hydrothermal reaction temperatures were tested by XRD, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Figure 8 The results showed that when the hydrothermal reaction temperature was 150°C, hydroxyapatite was formed on the surface of the titanium rod, but the purity of the hydroxyapatite was low, the crystallinity was weak, and there were unreacted impurities. When the hydrothermal reaction temperature was 180°C, the hydroxyapatite formed had high crystallinity, and the Ca, P, and O elements were evenly distributed on the surface of the titanium rod.

[0045] Example 4: Effect of hydrothermal reaction time on hydroxyapatite growth

[0046] The titanium rods with hydroxyapatite grown on their surfaces at different hydrothermal reaction times were tested by XRD, SEM and EDS. Figure 9 The results showed that when the reaction temperature was 180 ℃ and the reaction time was 12 h, no hydroxyapatite was formed on the surface of the titanium rod. When the reaction temperature was 180 ℃ and the reaction time was 24 h, hydroxyapatite titanium rods with high crystallinity, uniform distribution and uniform thickness were obtained.

[0047] Example 5: Effect of adjusting different pH values ​​on hydroxyapatite growth

[0048] The titanium rods with hydroxyapatite grown on their surfaces at different pH values ​​were tested by XRD, SEM and EDS. Figure 10 The results showed that when the reaction temperature was 180 ℃, the reaction time was 24 h, and the pH value was 7, hydroxyapatite did not grow successfully on the titanium rod surface. When the reaction temperature was 180 ℃, the reaction time was 24 h, and the pH value was 10, hydroxyapatite titanium rods with good surface morphology and high crystallinity were obtained.

Claims

1. A method for growing hydroxyapatite on a titanium rod based on a hydrothermal method, characterized in that: The method comprises the following steps: (1) Take a titanium rod, polish it until the surface is smooth to remove the surface oxide layer, and then clean the titanium rod; (2) Immerse the cleaned titanium rod in a 4-6 mol / L NaOH solution and react at 50-70 °C for 5-7 h to obtain a titanium rod with a porous surface; (3) Prepare a 0.5-0.9 mol / L hydroxyapatite precursor solution, adjust the pH to 10 with ammonia water, and continue stirring for 20-40 min; (4) After stirring, the hydroxyapatite precursor solution is transferred to a hydrothermal reactor, and the porous titanium rod obtained in step (2) is immersed therein. The reactor is then placed in a homogeneous reactor, and the temperature is raised to 170-200 °C at a rate of 4-6 °C / min and kept at this temperature for 18-30 h; (5) After the reaction is completed, the titanium rod is cleaned with anhydrous ethanol and deionized water and then dried.

2. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to claim 1, characterized in that: Step (1) is to use 600# and 2000# sandpaper to grind the titanium rod until the surface is smooth.

3. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to claim 1, characterized in that: The method for cleaning the titanium rod in step (1) is to use acetone, ethanol, and deionized water for ultrasonic cleaning in sequence for 10-20 minutes.

4. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to claim 1, characterized in that: The Ca / P atomic ratio of the hydroxyapatite precursor solution prepared in step (3) is 1.

67.

5. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to claim 1, characterized in that: The concentration of the hydroxyapatite precursor solution prepared in step (3) is 0.5-0.6 mol / L.

6. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to claim 1, characterized in that: In step (4), the reaction heating rate is controlled at 5 °C / min and the holding time is controlled at 22-24 h.

7. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to claim 1, characterized in that: The drying temperature in step (6) is 55-65°C and the drying time is 8-15 h.

8. The method for growing hydroxyapatite on a titanium rod based on a hydrothermal method according to any one of claims 1 to 7, characterized in that: The titanium rod is made of pure titanium or titanium alloy.